Phase transition of doped LaFeO3 anode in reducing atmosphere and their power generation property in intermediate temperature solid oxide fuel cell. (12th November 2019) - Ju, Young-Wan; Lee, SangWon; Kang, Byeong Su; Kim, Hack Ho; Ishihara, Tatsumi
Abstract: In general, transition metal-doped La0.6 Sr0.4 FeO3 (LSF) has been used as a cathode material for intermediate temperature solid oxide fuel cells (IT-SOFCs) because of its high mixed electronic−ionic conductivity and catalytic properties. Recently, some research groups have been investigating the doped LSF as an anode material. In this study, we evaluated the influence of dopant in LSF on anodic properties of LSF in SOFCs. Whereas Mn-doped LSF showed typical perovskite oxide structure even after reduction in hydrogen at high temperature, the LSF and Co-doped LSF exhibited phase transition partially to LaSrFeO4 and exsolution of metal particles after reduction. The phase transition and metal exsolution occurred at temperature higher than 1008 K in a reducing atmosphere. Despite the partial phase transition, the cell using Co-doped LSF anode exhibited fairly high power density of 1.33 W/cm 2 at 1173 K with the lowest polarization resistance. These results may originate from the high oxygen-ion conductivity of LaSrFeO4 –La(Sr)Fe(Co)O3 and the high hydrogen oxidation property of the Co–Fe particles on ceramic anode surface. Highlights: Influence of dopant on La0.5 Sr0.5 Fe0.9 Xo0.1 O3 -δ has been evaluated. LSF and LSFC exhibited partial phase transition to LaSrFeO4 after reduction. LSFC showed highest power generation properties by exsolution of Co–Fe particle. The phase transition and metal exsolution occurs at higher temperature than 1008 K.